2020
DOI: 10.1080/14681811.2020.1766435
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the ‘C’ in CSE: implementation and effectiveness of comprehensive sexuality education in the WHO European region

Abstract: The purposes of this paper are: to assess how comprehensive sexuality education (CSE) is implemented in schools in the World Health Organisation's European Region; and to investigate the evidence supporting its effectiveness. Data were collected in 2016-2017, using a validated questionnaire sent to representatives of governmental and nongovernmental institutions in 25 countries of the WHO European Region. Theresults demonstrated that, in nine countries, sexuality education can be classified as comprehensive; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 3 publications
(2 reference statements)
0
8
0
1
Order By: Relevance
“…We included studies from the 53 European and Central Asian member states of the WHO European Region since the scoping review was conducted within the framework of engagement of the German Federal Centre for Health Education (BZgA), which is the WHO Collaborating Centre for Sexual and Reproductive Health for the WHO European Region. Our systematic review was designed to build on the WHO European Region's vision on sexuality education 1 which The Centre it has been promoting for the past decade (Ketting, Brockschmidt, and Ivanova 2020;Ketting 2018; WHO Regional Office for Europe and Federal Centre for Health Education 2010). It forms the basis of a guidance document for policymakers and programmers of sexuality education for children and young people with disabilities that will be published by WHO for the European Region.…”
Section: Geographical Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…We included studies from the 53 European and Central Asian member states of the WHO European Region since the scoping review was conducted within the framework of engagement of the German Federal Centre for Health Education (BZgA), which is the WHO Collaborating Centre for Sexual and Reproductive Health for the WHO European Region. Our systematic review was designed to build on the WHO European Region's vision on sexuality education 1 which The Centre it has been promoting for the past decade (Ketting, Brockschmidt, and Ivanova 2020;Ketting 2018; WHO Regional Office for Europe and Federal Centre for Health Education 2010). It forms the basis of a guidance document for policymakers and programmers of sexuality education for children and young people with disabilities that will be published by WHO for the European Region.…”
Section: Geographical Regionmentioning
confidence: 99%
“…This aligns with findings from Ketting, Brockschmidt, and Ivanova's (2020) recent study of implementation of CSE implementation in the WHO European Region, which only identified two CSE programmes outside of northwestern Europe (in the Czech Republic and Estonia). The authors concluded that 'in southern and southeastern Europe and in Central Asia, CSE programmes are yet to be seen' (Ketting, Brockschmidt, and Ivanova 2020); hence it is unsurprising that no programmes specifically targeting children and young people with disabilities could be identified. This is an important research gap, particularly given the important influence of culture on sexuality and disability, as well as culturally diversity in the WHO European Region.…”
Section: Gaps In Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleasure and desire are largely absent within sex and relationship education [ 71 ] and, when they are included, they are often proposed as part of a discourse on safe practice, where pleasure continues to be equated with danger [ 72 ]. The persistent absence of a “discourse of desire” in sex education [ 73 , 74 ] is especially problematic for women, for whom desire is still mediated by (positive) male attention, and for whom pleasure is derived from being found desirable and not from sexual self-expression or from their own desires [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are gaps: according to the Guttmacher Institute [29], only 2% of students indicate having received CSE; teachers claim 75% of schools provide it. Successfully implementing CSE does require teacher training and development of material lesson planning, suggested a comparison of European countries which had implemented CSE to those that have not [56]. In Kenya, this means that a nationwide commitment to CSE-roll-out would need to include culturally PLOS ONE appropriate education and sensitization for teachers and other stakeholders such as parents to ensure their alignment and improve their commitment to providing learners with CSE.…”
Section: Srhr Knowledge: Internet and Schools Are An Opportunitymentioning
confidence: 99%